Diastereomers of the Anticancer Peptide CIGB-300 with Altered β-Turn Structures - Celia G. Moya; Rafael Rodriguez; Carlos S. Perez; Hilda Garay; Julian Wiesent; Stefan Gröger; Yordanka Masforrol; Yasser Perera; Silvio E. Perea; Jochen Balbach (International Journal of Peptide Research and Therapeutics, 2024)
Purpose The next-generation anti-tumor drug peptide CIGB-300, developed by the Center for Genetic Engineering and Biotechnology (CIGB), targets casein kinase 2 (CK2) and its substrates, implicating significant therapeutic potential in cancer treatment. A key focus of this study was to compare CIGB-300 and a primary synthetic byproduct, CIGB-300iso, which shares the amino acid sequence with CIGB-300 but was proposed to differ due to racemization. Methods This study explores the synthesis, characterization, and structural elucidation of CIGB-300 and its isomer CIGB-300iso by a comprehensive NMR analysis of seven synthesized diastereomers including amino acid residues C15, H21, and C25. Results This study revealed that CIGB-300iso contains one D enantiomer at position H21. The structures of both isoforms derived from NMR constraints disclosed that the L and D enantiomers have an altered peptide supersecondary structure, with a β-turn type IV 3 found in CIGB-300 and a type I β-turn in CIGB-300iso. Conclusion The configuration of H21 significantly impacts the peptide’s conformations, sidechain orientations and, potentially, its biological activity. These findings highlight the importance of enantiomerically pure peptides for the design and synthesis of drug peptides.

The presence of membranes or micelles induces structural changes of the myristoylated guanylate-cyclase activating protein-2 - Stephan Theisgen; Lars Thomas; Thomas Schröder; Christian Lange; Michael Kovermann; Jochen Balbach; Daniel Huster (European Biophysics Journal, 2011)

Combined NMR-observation of cold denaturation in supercooled water and heat denaturation enables accurate measurement of ΔC p of protein unfolding - Thomas Szyperski; Jeffrey L. Mills; Dieter Perl; Jochen Balbach (European Biophysics Journal, 2006)